Enhancement of the dielectric permittivity and magnetic properties of Dy substituted strontium titanate ceramics. Issue 2 (February 2018) - Tkach, Alexander; Amaral, João S.; Zlotnik, Sebastian; Amaral, Vítor S.; Vilarinho, Paula M.
Abstract: Structural, dielectric and magnetic properties of dense Dy-substituted strontium titanate ceramics are investigated. In the Sr1-1.5 x Dy x TiO3 system, incorporation of Dy onto the Sr site is confirmed by a linear decrease of the lattice parameter up to x  = 0.05. Dielectric spectroscopy analysis of Sr1-1.5 x Dy x TiO3 ceramics reveals four relaxations. Two relaxations observed below 55 K are attributed to dipoles formed by off-centre displacement of Dy 3+ ions on the Sr sites. Other two dielectric relaxations found at higher temperatures are attributed to the oxygen vacancy related mechanisms. As result, very high dielectric permittivity of ∼33500 at 28 K and of ∼9600 around room temperature at moderate dissipation factor of ∼0.02 are obtained for Sr0.985 Dy0.01 TiO3 ceramics, making it a promising material for capacitor electronic applications. Paramagnetic behaviour observed for Sr1-1.5 x Dy x TiO3 as well as for Sr1- x Dy2 x Ti1- x O3 ceramics indicates impossibility to induce a magnetic order and hence magnetoelectric coupling in strontium titanate by Dy substitution.